WAKTU TUNGGU PELAYANAN RESEP DI DUA PUSKESMAS KABUPATEN TEGAL - Adila Prabasiwi; Sari Prabandari; Arda Kusuma Dewi; Oktaviani Nihlatuzzahroh (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
Dispensary waiting time is one of the factors that causes patient dissatisfaction. This study aims to determine the waiting time for prescription services in two selected Puskesmas in Tegal Regency.This research was included in a descriptive study with a quantitative approach. The study was conducted in two selected Puskesmas in Tegal Regency.The sample is a recipe that was served in a pharmaceutical installation in February totaling 200 recipes using the quota sampling method. Dispensary waiting time is taken using a stopwatch tool. Data analysis using univariate and bivariate analysis. Univariate analysis by describing the overall waiting time, while bivariate analysis uses a t-test to see the difference in dispensary waiting time.The results showed that there were differences in the average waiting time for non concoction recipe)and concoction recipe (p = 0,000). The average dispensary waiting time for non concoction is 9 minutes 5 seconds, for concoction drugs 17 minutes 28 seconds. There is a difference in dispensary waiting time for non concoction and concoction drugs between Puskesmas X and Puskesmas Y (p = 0,000). The waiting time for prescription services at Puskesmas X is 14 minutes 45 seconds (non concoction recipe) and 21 minutes 3 seconds (concoction recipe). The dispensary waiting time at Puskesmas Y is 5 minutes 5 seconds (non concoction recipe) and 10 minutes 25 seconds (concoction recipe)Keywords: Dispensary waiting time, recipes, non concoction recipe, concoction recipe, puskesmas.